PROTOTYPE ROBOT CERDAS PEMOTONG RUMPUT BERBASIS RASPBERRY Pi B+ MENGGUNAKAN WEB BROWSER - Diah Aryani; Muhamad Wahyudin; Muhammad Fazri (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2015)
Current science and technology are developing by leaps and bounds thus providinggreat benefits in all aspects of human life including the robot-a robot designed toassist human tasks through supervision and human control, or use the program. The development of grass that propagate ground quickly often make nursing groundshave to mow the lawn with regular intensive. Related to this, then the tool in the form of a single intelligent robot cutting grass-based Pi B+ raspberry is the application ofrobotic systems that aim to control 2 motor Driver l298n useful for running gear boxwheel robots and grass cutters on Dynamo cutting tools lawns without a crew. The programming language used is the language which has been running pyton Apache Web Server. So by designing Intelligent robot prototype lawnmowing rasbery Pibased B+ using a web browser at the time grass has begun to grow tall, grass-cuttingIntelligent robot can directly perform cutting grass with a controlled web browser.